Pendekatan Klinis Perawatan Indirect Pulp Capping bagi Pelajar - Sofiani, Erma; Nurhasanah, Maulida; Orienty, Fauzia Nilam (Universitas Muhammadiyah Yogyakarta, 2023)
Cavities or caries are diseases of the hard tissue of the teeth. The presence of caries must not be ignored and must be treated because carious lesions can spread and result in pain, tooth loss, and infection of the tissues supporting the teeth. This community service activity aims to increase public awareness of dental and oral health through curative efforts and evaluation of the clinical picture after indirect pulp capping treatment at the State Agricultural Development Vocational School, Ikurkoto Health Center Area, Padang City. The method used in this service begins with patient screening, pulp capping treatment, and evaluation in the form of subjective and objective examinations 1 week after treatment. Participants in the activity were 403 patients who came from around the Ikurkoto Community Health Center area. This activity found that cavities were more common in the back (posterior) teeth, especially the lower molars, as much as 80%, compared to the front (anterior) teeth, as much as 20%. The material used is a bioactive material, namely Glass Ionomer Cement (SIK) type 2 with different brands, namely Fuji II LC (type II aesthetic) 70% and Fuji IX (type II reinforced) 30%. The evaluation results after treatment showed that as many as 71% of dental patients were asymptomatic and responded well to pulp capping treatment.